An Analysis of Online Learning's Effectiveness in Improving Learning Independence and Critical Thinking Skillsin Higher Education Students - Budi Santoso; Aulia Pratama (PT. Technology Laboratories Indonesia (TechnoLabs), 2024)
This study investigates the effectiveness of online learning in enhancing learning independence and critical thinking skills among higher education students. Using a mixed-methods approach, the research was conducted over a semester with 200 undergraduate students, divided into an experimental group engaged in online learning and a control group receiving traditional instruction. The findings revealed that the experimental group exhibited significant improvements in both learning independence and critical thinking skills compared to the control group. Qualitative data further supported these results, highlighting the benefits of autonomy, flexibility, and interactive content in online learning. However, challenges related to maintaining student motivation were also identified, indicating the need for more engaging and supportive online learning environments. These findings suggest that, while online learning can effectively foster essential academic skills, careful consideration must be given to course design to maximize its benefits.